2017
DOI: 10.5761/atcs.oa.17-00020
|View full text |Cite
|
Sign up to set email alerts
|

Difference in Postsurgical Prognostic Factors between Lung Adenocarcinoma and Squamous Cell Carcinoma

Abstract: IntroductionLung adenocarcinoma (AD) and squamous cell carcinoma (SQ) are the two major histologic types of nonsmall-cell lung cancer (NSCLC), and have been considered to be almost similar in both postsurgical prognosis and chemotherapeutic responses for a long period of time. However, recent multiple studies on the postsurgical outcomes of these two histologic types Difference in Postsurgical Prognostic Factors between Lung Adenocarcinoma and Squamous Cell CarcinomaHaruhiko Nakamura, MD, PhD, Hiroki Sakai, MD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 30 publications
2
21
0
Order By: Relevance
“…Molinier et al [24] estimated 5year survival in non-small-cell lung cancer patients and found that smoking level at diagnosis was an independent negative prognostic factor in LUSC patients. Nakamura et al [25] performed the multivariate analysis to find that smoking in LUSC was associated with recurrence-free survival. Although without distinguishing histological type, a cohort claimed that recent quitting could decrease the risk of death among patients with lung cancer (HR, 0.90; 95% CI 0.81-0.99) [11].…”
Section: Discussionmentioning
confidence: 99%
“…Molinier et al [24] estimated 5year survival in non-small-cell lung cancer patients and found that smoking level at diagnosis was an independent negative prognostic factor in LUSC patients. Nakamura et al [25] performed the multivariate analysis to find that smoking in LUSC was associated with recurrence-free survival. Although without distinguishing histological type, a cohort claimed that recent quitting could decrease the risk of death among patients with lung cancer (HR, 0.90; 95% CI 0.81-0.99) [11].…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, no difference was found when we analysed DFS, but, among those who had a recurrence, those with squamous cell carcinoma had a significantly worse survival. A worse survival with a concomitant, similar DFS for patients with squamous cell carcinoma compared to adenocarcinoma has been reported by other authors [21][22][23], who concluded that the difference in the mortality rate might be associated with noncancer-related causes; nevertheless, Fukui et al found more deaths among patients with a recurrent squamous cell carcinoma than among those with adenocarcinoma. They, therefore, proposed a reclassification of T1a-bN0 and T2N0 squamous cell NSCLC as Stage IIA.…”
Section: Discussionmentioning
confidence: 72%
“…Molinier et al (27) estimated five-year survival in non-small-cell lung cancer patients and found that smoking level at diagnosis was an independent negative prognostic factor in LUSC patients. Nakamura et al (28) performed the multivariate analysis to find that smoking in LUSC was associated with recurrence-free survival. Although without distinguishing histological type, a cohort claimed that recent quitting could decrease the risk of death among patients with lung cancer (HR, 0.90; 95% CI 0.81-0.99) (11).…”
Section: Discussionmentioning
confidence: 99%